Convergence of Maqashid Syariah, Hifzul Bi’ah and Islamic Stock Index - Wiku Suryomurti; Fakhrudin Fakhrudin; Muhammad Isa Mustafa (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
This study aims to explore the urgency of converging the principles of environment protection and Sustainable Responsible Investment from the perspective of Maqashid Syariah into the selection process of Islamic Stock Index. In-depth analysis on current literature practices on Maqashid Syariah, hifdzul bi’ah and Islamic stock index. The convergence of Maqashid Syariah, in particular Hifzul Bi’ah and stock index screening process will allow a creation of a new Islamic index or rejuvenating current Islamic stock index in Indonesia. We suggest that Dewan Syariah Nasional to start implementing Maqashid Syariah and Hifzul Bi’ah principle in the process of stock screening for Islamic Stock Indexes. This study is among the first of its kind to offer integration of Maqashid Syariah in particular Hifzul Bi’ah to the Islamic stock index.